ANALISIS PENERAPAN KOMPETENSI KARYAWAN DALAM MENGATASI TINGKAT KECELAKAAN KERJA (Studi Kasus Pada Operator Unit Alat Berat Pt. Kaltim Diamond Coal Site Loa Gagak) - Imanuel Sulo (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2021)
This study aims to analyze and determine the implementation of employee competence in overcoming the level of accidents at heavy equipment operator PT Kaltim Diamond Coal. Competence (X) is used as the dependent variable while Work Accident (Y) is the dependent variable. Primary data were obtained through data available at PT Kaltim Diamond Coal. The results showed that employee competence increases employee awareness to be able to work safely, so as to reduce the level of potential hazards that occur at work. Knowledge enables employees to be able to recognize each work tool and also improves employee analysis skills, skills enable an employee to carry out each unit worked, and attitudes increase employee commitment to work so that they are able to act according to correct work procedures, so as to avoid potential work accidents. PT Kaltim Diamond Coal should improve the competence of each employee with the aim of increasing the ability of employees to carry out their responsibilities in accordance with work procedures, so as to avoid any dangerous actions that can lead to work accidents.